Osteoinduction of biphasic calcium phosphate scaffolds in a nude mouse model. (October 2014) - Miramond, T; Corre, P; Borget, P; Moreau, F; Guicheux, J; Daculsi, G; Weiss, P
Bioceramics combined with isolated stem cells, or with total bone marrow, constitute the main strategies under consideration in the field of bone tissue engineering. In the present preclinical study, two biphasic calcium phosphate scaffolds currently on the market, MBCP® and MBCP+®, with different hydroxyapatite/β-tricalcium phosphate ratio, were implanted ectopically in a nude mouse model. These scaffolds were supplemented either with human mesenchymal stromal cells, or with human total bone marrow, or rat total bone marrow. Biomaterials alone were found to have potentially low, but non-zero, osteoinductive properties, while biomaterials associated with total bone marrow consistently improved osteoinduction in comparison with high concentrations of isolated human stromal cells.